Research and support activities for elite athletes of JISS - Kubo, Y. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
Twelve years have passed from starting operations of the Japan Institute of Sports Sciences (JISS). We have been tasked with improving the competitiveness of Japanese elite athletes in international sports on the basis of the evidences of sports medicine, sports science and sports intelligence. To carry out that mission, we operate a number of programs, including: a medical-scientific research program, a medical-scientific support program and a sports clinic program. The purposes of the paper are to review of past works in these programs and to show future issue of JISS.